Tolerance to drought of coffee trees produced by cuttings and somatic embryogenesis - Dominghetti, Anderson William; Souza, Antônio Jackson de Jesus; Silveira, Helbert Rezende de Oliveira; Sant’Ana, José Antônio do Vale; de Souza, Kamila Rezende Dázio; Guimarães, Rubens José; Lacerda, Jordana Reis (Coffee Science - ISSN 1984-3909, 2016)
The irrigation in coffee plantations is the focus of research for many years, but the new seedling production technologies (somatic embryogenesis and cuttings) have demanded new behavioral studies of these in the field and their water needs. An experiment was carried out in a greenhouse at the Federal University of Lavras, Lavras - MG, Brazil, aiming at to evaluate the tolerance to drought of coffee coming from seedlings produced by somatic embryogenesis and cutting, the culture of the deployment phase. The experimental design was a randomized complete block design with five replicates, factorial 2 x 5 with two types of seedlings produced by somatic embryogenesis and cuttings, and five levels of irrigation, based on the maintenance of soil field capacity 20%, 40%, 60%, 80% and 100%. At 153 days after beginning of the experiment were evaluated foliar contents proline, leaf water potential, plant height, stem diameter, leaf area, dry weight of roots and shoots. It was found that coffee originated from cuttings and somatic embryogenesis positively and increasingly respond to irrigation. It was also found that the field capacity maintained below 74.6% to 100% coffee derived somatic embryogenesis of seedlings and cuttings, respectively, harm the growth and initials development of plants.